Circular RNA cSMARCA5 regulates the progression of cervical cancer by acting as a microRNA-432 sponge - Huang, Ping (Mol Med Rep, 2020)
Circular RNAs (circRNAs) have been shown to be involved in the development of cancer. The aim of the present study was to investigate the role of circRNA SMARCA5 (cSMARCA5) in human cervical cancer. In the present study, cSMARCA5 expression was upregulated in cervical cancer tissues and cell lines. Furthermore, the proliferation rate of cells transduced with viral plasmids expressing small interfering RNA targeting cSMARCA5 was downregulated. Bioinformatics analysis predicted that microRNA (miR)-432 targeted cSMARCA5, and miR-432 was able to interact with epidermal growth factor receptor (EGFR) by binding to its 3′-untranslated region. The expression levels of EGFR, ERK1 and ERK2 were increased in cervical cancer tissues. Furthermore, correlation analysis revealed that cSMARCA5 levels were positively correlated with ERK1 and ERK2 levels. In conclusion, the present findings suggested that cSMARCA5 may play an important role in the progression of cervical cancer via the ERK signaling pathway by modulating miR-432.